Management Guidelines for Business Operations under the BCG Economy Concept: A Study of Small and Medium Enterprises (SMEs) in Nong Khaem District, Bangkok, Thailand - Shangkomshome, Thanawan; Tanskul, Kawissara; Davis, Murray (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to develop management guidelines for business operations under the BCG Economy concept. The study used a qualitative research methodology, collecting data from 30 key informants—SME entrepreneurs in Nong Khaem District, Bangkok—through in-depth interviews. The interview tool was a semi-structured questionnaire, which was validated by experts in terms of structure and content. The data from the interviews were analyzed using content analysis to extract key insights. The findings of the study revealed that the majority of SME entrepreneurs in Nong Khaem District, Bangkok, had an average age of 37.87 years and an average of 11.57 years of work experience. Most entrepreneurs had a bachelor’s degree, and the majority of businesses were in manufacturing, with the business size ranging from 100 to 500 million baht. The interview data showed the following points. 1) Most entrepreneurs understood the management guidelines on their businesses according to the BCG Economy concepts. 2) The main problems were the shortage of raw materials, the lack of skilled labor that met the needs of businesses, and the difficulties in securing funding to invest in business transformation to align with the BCG Economy, which required high investment. This included redesigning products according to this policy. 3) Regarding business operations under the BCG Economy concept, most entrepreneurs agreed with the implementation of Circular Economy policies, particularly reusing and recycling of materials such as packaging. 4) The key success factors for managing businesses under the BCG Economy concept included the ability to achieve significant business growth and sustainability.